Pedagogical Possibilities Of Creating And Evaluating Mathematical Tests Based On Artificial Intelligence - Zahrooy Tokhirova (Euro Asian Journal Publishing, 2025)
This article explores the role of artificial intelligence (AI) technologies in mathematics education, focusing on the use of the iSpring platform for creating and assessing tests. It analyzes how AI can assist in automatically generating test questions, evaluating student performance, and providing personalized learning recommendations. In addition to highlighting the benefits of AI integration in education, the paper also discusses its limitations and necessary precautions
Keywords: artificial intelligence; mathematics education; test creation